Stimulus responsive graphene scaffolds for tissue engineering - Almeida, Sofia S. (2016)
Tissue engineering (TE) is an emerging area that aims to repair damaged tissues and organs by combining different scaffold materials with living cells. Recently, scientists started to engineer a new generation of nanocomposite scaffolds able to mimic biochemical and biophysical mechanisms to modulate the cellular responses promoting the restoration of tissue structure or function. Due to its unique electrical, topographical and chemical properties, graphene is a material that holds a great potential for TE, being already considered as one of the best candidates for accelerating and guiding stem cell differentiations. Although this is a promising field there are still some challenges to overcome, such as the efficient control of the differentiation of the stem cells, especially in graphene-based microenvironments. Hence, this chapter will review the existing research related to the ability of graphene and its derivatives (graphene oxide and reduced graphene oxide) to induce stem cell differentiation into diverse lineages when under the influence of electrical, mechanical, optical and topographic stimulations.